Probiotic potential of indigenous yeasts isolated during the fermentation of table olives from Northeast of Portugal - Oliveira, Tatiane C.G. (2017)
The aim of this study was to evaluate the probiotic potential of 16 yeast strains previously isolated during the natural fermentation of table olives Negrinha de Freixo cultivar, in relation to enzymatic activities; ability to grow at 37 °C; antimicrobial activity; autoaggregation capacity; antioxidant activity and survival in gastrointestinal tract conditions. The highest antioxidant activity was observed for Saccharomyces cerevisiae, similar to the reference strain S. boulardii. Candida norvegica 7A and Galactomyces reessii 34A showed antifungal ability to the pathogenic microorganism Cryptococcus neoformans. Regarding the autoaggregation capacity, S. cerevisiae 15A, C. tropicalis 1A and C. norvegica 7A showed > 80% after 24 h. Pichia guilliermondii 25A and C. norvegica 7A were the most resistant to the simulated digestive conditions, similar to the reference strain (S. boulardii). Thus, these results suggest that some yeast strains involved in the fermentation of table olives have probiotic potential. Industrial relevance In this study, we highlight the probiotic potential of yeast microbiota usually found in green table olives. These yeast strains could be used as culture starters for the development of new functional products.